Is the Interplay between Epigenetic Markers Related to the Acclimation of Cork Oak Plants to High Temperatures? - Correia, Barbara; Valledor, Luis; Meijón, Mónica; Rodriguez, José Luis; Dias, Maria Celeste; Santos, Conceição; Cañal, Maria Jesus; Rodriguez, Roberto; Pinto, Glória (PLoS ONE, 2013)
Trees necessarily experience changes in temperature, requiring efficient short-term strategies that become crucial in environmental change adaptability. DNA methylation and histone posttranslational modifications have been shown to play a key role in both epigenetic control and plant functional status under stress by controlling the functional state of chromatin and gene expression. Cork oak (Quercus suber L.) is a key stone of the Mediterranean region, growing at temperatures of 45°C. This species was subjected to a cumulative temperature increase from 25°C to 55°C under laboratory conditions in order to test the hypothesis that epigenetic code is related to heat stress tolerance. Electrolyte leakage increased after 35°C, but all plants survived to 55°C. DNA methylation and acetylated histone H3 (AcH3) levels were monitored by HPCE (high performance capillary electrophoresis), MS-RAPD (methylation-sensitive random-amplified polymorphic DNA) and Protein Gel Blot analysis and the spatial distribution of the modifications was assessed using a confocal microscope. DNA methylation analysed by HPCE revealed an increase at 55°C, while MS-RAPD results pointed to dynamic methylation-demethylation patterns over stress. Protein Gel Blot showed the abundance index of AcH3 decreasing from 25°C to 45°C. The immunohistochemical detection of 5-mC (5-methyl-2′-deoxycytidine) and AcH3 came upon the previous results. These results indicate that epigenetic mechanisms such as DNA methylation and histone H3 acetylation have opposite and particular dynamics that can be crucial for the stepwise establishment of this species into such high stress (55°C), allowing its acclimation and survival. This is the first report that assesses epigenetic regulation in order to investigate heat tolerance in forest trees.
The following values have no corresponding Zotero field: publisher: Public Library of Science accession-num: 23326451
Keywords: Acclimatization; Acclimatization: genetics; Acetylation; Blotting; CHROMATIN; CORK oak (citation; Deoxycytidine; Deoxycytidine: analogs & derivatives; Deoxycytidine: metabolism; DNA; DNA methylation; Electrolytes; Electrolytes: metabolism; Epigenesis; Gene expression; Genetic; Genetic Markers; Genome; Heat-Shock Response; Heat-Shock Response: genetics; Histones; Histones: metabolism; Physiological; Physiological: genetics; Plant; Plant Leaves; Plant Leaves: metabolism; Plant: genetics; POST-translational modification; Quercus; Quercus: genetics; Quercus: physiology; Random Amplified Polymorphic DNA Technique; Stress; tags); Temperature; TREES -- Research; Western

Isoscapes of tree-ring carbon-13 perform like meteorological networks in predicting regional precipitation patterns - del Castillo, Jorge; Aguilera, Monica; Voltas, Jordi; Pedro Ferrio, Juan (JOURNAL OF GEOPHYSICAL RESEARCH-BIOGEOSCIENCES, 2013)
Stable isotopes in tree rings provide climatic information with annual resolution dating back for centuries or even millennia. However, deriving spatially explicit climate models from isotope networks remains challenging. Here we propose a methodology to model regional precipitation from carbon isotope discrimination (Delta C-13) in tree rings by (1) building regional spatial models of Delta C-13 (isoscapes) and (2) deriving precipitation maps from Delta C-13-isoscapes, taking advantage of the response of Delta C-13 to precipitation in seasonally dry climates. As a case study, we modeled the spatial distribution of mean annual precipitation (MAP) in the northeastern Iberian Peninsula, a region with complex topography and climate (MAP = 303-1086 mm). We compiled wood Delta C-13 data for two Mediterranean species that exhibit complementary responses to seasonal precipitation (Pinus halepensis Mill., N = 38; Quercus ilex L.; N= 44; pooling period: 1975-2008). By combining multiple regression and geostatistical interpolation, we generated one Delta C-13-isoscape for each species. A spatial model of MAP was then built as the sum of two complementary maps of seasonal precipitation, each one derived from the corresponding Delta C-13-isoscape (September-November from Q. ilex; December-August from P. halepensis). Our approach showed a predictive power for MAP (RMSE = 84 mm) nearly identical to that obtained by interpolating data directly from a similarly dense network of meteorological stations (RMSE = 80-83 mm, N= 65), being only outperformed when using a much denser meteorological network (RMSE = 56-57 mm, N = 340). This method offers new avenues for modeling spatial variability of past precipitation, exploiting the large amount of information currently available from tree-ring networks.
CitationCitationThe following values have no corresponding Zotero field: pub-location: 2000 FLORIDA AVE NW, WASHINGTON, DC 20009 USA publisher: AMER GEOPHYSICAL UNION
Keywords: ARCHAEOBOTANICAL REMAINS; ATMOSPHERIC CO2; CARBON-ISOTOPE DISCRIMINATION; climate; DELTA-C-13; PINUS-HALEPENSIS; RAINFALL; STABLE-ISOTOPES; Temperature

Seasonal and inter-annual variability of bud development as related to climate in two coexisting Mediterranean Quercus species - Alla, Arben Q.; Camarero, J. Julio; Montserrat-Martí, Gabriel (Annals of Botany, 2013)
Background and Aims In trees, bud development is driven by endogenous and exogenous factors such as species and climate, respectively. However, knowledge is scarce on how these factors drive changes in bud size across different time scales.Methods The seasonal patterns of apical bud enlargement are related to primary and secondary growth in two coexisting Mediterranean oaks with contrasting leaf habit (Quercus ilex, evergreen; Quercus faginea, deciduous) over three years. In addition, the climatic factors driving changes in bud size of the two oak species were determined by correlating bud mass with climatic variables at different time scales (from 5 to 30 d) over a 15-year period.Key Results The maximum enlargement rate of buds was reached between late July and mid-August in both species. Moreover, apical bud size increased with minimum air temperatures during the period of maximum bud enlargement rates.Conclusions The forecasted rising minimum air temperatures predicted by climatic models may affect bud size and consequently alter crown architecture differentially in sympatric Mediterranean oaks. However, the involvement of several drivers controlling the final size of buds makes it difficult to predict the changes in bud size as related to ongoing climate warming.
10.1093/aob/mcs24710.1093/aob/mcs247
Keywords: Bud size; current-year stem; Quercus faginea; quercus ilex subsp. ballota; summer growth; Temperature

Temperature-induced structural and chemical changes in cork from Quercus cerris - Şen, Ali; Miranda, Isabel; Pereira, Helena (Industrial Crops and Products, 2012)
The effects of temperature on anatomical and chemical characteristics of Quercus cerris cork were examined. Cork samples were subjected to isothermal air heating between 150 ◦ C and 400 ◦ C and analyzed for mass loss, cellular structure and chemical composition. The thermal decomposition of Q. cerris cork is similar to that of Q. suber cork. Cork is thermally stable below 200 ◦ C and after that degradation depended on temperature and heating time with increasing mass loss, i.e. 3% at 200 ◦ C 10min and 46% at 350 ◦ C 60min.With temperature and starting at 200 ◦ C, cells expanded, cell wall thickness was reduced and corrugations were lost. Extractives degraded at lower temperatures, although aliphatic extractives were found to be more stable. Suberin from Q. cerris was more heat resistant than Q. suber suberin, while lignin showed similar resistance. These results provide a basis for studies on the production of Q. cerris bark expanded cork agglomerates for insulation purposes.
Keywords: Cellular structure; Cork; Quercus cerris; suberin; Temperature

Unveiling the fungal mycobiota present throughout the cork stopper manufacturing process - Barreto, Maria C; Houbraken, Jos; Samson, Robert A; Brito, Dulce; Gadanho, Mário; San Romão, Maria V (FEMS Microbiology Ecology, 2012)
A particular fungal population is present in the main stages of the manufacturing process of cork discs. Its diversity was studied using both dependent (isolation) and independent culture methods (denaturing gel gradient electrophoresis and cloning of the ITS1-5.8S-ITS2 region). The mycobiota in the samples taken in the stages before and after the first boiling seems to be distinct from the population in the subsequent manufacturing stages. Most isolated fungi belong to the genera Penicillium, Eurotium and Cladosporium. The presence of uncultivable fungi, Ascomycota and endophytes in raw cork was confirmed by sequencing. The samples taken after the first boiling contained uncultivable fungi, but in a few samples some isolated fungi were also detected. The main taxa present in the following stages were Chrysonilia sitophila, Penicillium glabrum and Penicillium spp. All applied techniques had complementary outcomes. The main factors driving the shift in cork fungal colonization seem to be the high levels of humidity and temperature to which the slabs are subjected during the boiling process.
Keywords: Biodiversity; cloning; Cork; denaturing gel electrophoresis; Denaturing Gradient Gel Electrophoresis; DNA; Fungal; Fungal: genetics; fungi; Fungi: classification; Fungi: isolation & purification; humidity; Industry; Metagenome; mycobiota diversity; Penicillium; Penicillium: classification; Penicillium: isolation & purification; phylogeny; Plant Bark; Plant Bark: microbiology; Portugal; Quercus; Quercus: microbiology; Ribosomal Spacer; Ribosomal Spacer: genetics; Spain; Temperature; uncultivable fungal species

Why only some plants emit isoprene. - Monson, Russell K.; Jones, Ryan T.; Rosenstiel, Todd N.; Schnitzler, Jörg-Peter (Plant, cell & environment, 2012)
Isoprene (2-methyl-1,3-butadiene) is emitted from many plants and it appears to have an adaptive role in protecting leaves from abiotic stress. However, only some species emit isoprene. Isoprene emission has appeared and been lost many times independently during the evolution of plants. As an example, our phylogenetic analysis shows that isoprene emission is likely ancestral within the family Fabaceae (= Leguminosae), but that it has been lost at least 16 times and secondarily gained at least 10 times through independent evolutionary events. Within the division Pteridophyta (ferns), we conservatively estimate that isoprene emissions have been gained five times and lost two times through independent evolutionary events. Within the genus Quercus (oaks), isoprene emissions have been lost from one clade, but replaced by a novel type of light-dependent monoterpene emissions that uses the same metabolic pathways and substrates as isoprene emissions. This novel type of monoterpene emissions has appeared at least twice independently within Quercus, and has been lost from 9% of the individuals within a single population of Quercus suber. Gain and loss of gene function for isoprene synthase is possible through relatively few mutations. Thus, this trait appears frequently in lineages; but, once it appears, the time available for evolutionary radiation into environments that select for the trait is short relative to the time required for mutations capable of producing a non-functional isoprene synthase gene. The high frequency of gains and losses of the trait and its heterogeneous taxonomic distribution in plants may be explained by the relatively few mutations necessary to produce or lose the isoprene synthase gene combined with the assumption that isoprene emission is advantageous in a narrow range of environments and phenotypes.
The following values have no corresponding Zotero field: accession-num: 22998549
Keywords: Drought; ferns; phloem; phylogeny; substrate; Temperature; thermotolerance; ﬁtness

Scavenging in Mediterranean ecosystems: effect of the invasive Argentine ant - Angulo, Elena; Caut, Stéphane; Cerdá, Xim (Biological Invasions, 2011)
Above-ground invertebrates may represent a high proportion of animal biomass, but few data are available on their fate after death. In Mediterranean ant communities, they are frequently scavenged by ants. Here, we assessed the consequences of Argentine ant invasion on the removal of arthropod corpses in Don˜ana National Park (SW Spain). In three natural habitats that differed in their degree of vegetation cover (i.e. protection for ants against high temperatures), we experimentally provided dead Drosophila, and observed their disappearance over a 60-min period at different times of day and year. The habitats used were isolated cork oak trees, pine tree forest and dry scrubland; we compared invaded with uninvaded plots in each. Oak trees were the most invaded habitat, while scrubland was the least and the only one where the Argentine ant coexisted with native ant species. In accordance with this degree of invasion, the Argentine ant removed the highest percentage of dead ﬂies in oak trees and the lowest in scrubland. Its performance as scavenger was higher than uninvaded ant communities, but it was reduced at high temperatures, when native species were highly efﬁcient. The saturated distribution of the Argentine ant colony seems to be the key to its efﬁciency. We discuss how the occurrence and scavenger efﬁciency of the Argentine ant could affect the nutrient cycling and the progression of its invasion.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: á; Ant communities; Arthropod corpses; Doñana; Linepithema humile; linepithema humile á don; Temperature; temperature á ant communities

Mismatch between the timing of oviposition and the seasonal optimum. The stochastic phenology of Mediterranean acorn weevils - Bonal, Raul; Muñoz, Alberto; MARÍA ESPELTA, JOSEP (Ecological Entomology, 2010)
1. The timing of reproduction is predicted to match the period of maximum food availability. In this sense, the case of many phytophagous insects in temperate regions is very illustrative, as their larvae usually depend on a resource only available for a limited period of time each year. 2. For 3 years the interactions between the weevil Curculio elephas and the Mediterranean Holm oak Quercus ilex were studied. Weevil larvae grow within the acorns, feeding on the cotyledons. The timing of oviposition will determine food availability for the larvae, as acorns stop growing once they are attacked. 3. Acorn temporal growing patterns did not change between years and food availability for larvae was at its highest in October, when temperature was still suitable for larval development. However, oviposition phenology did change between years. In 2002 females oviposited later, larvae grew within larger acorns, and their body mass was significantly higher than in 2003 or 2004, when females oviposited into early acorns. 4. Thus, weevils do not always adjust oviposition to the best possible feeding conditions for their offspring. Rather, they seem to maximise their own lifetime fitness, ovipositing as soon as they emerge in late summer. Emergence, in turn, depends strongly on stochastic events such as summer storms in the Mediterranean region. 5. Under a climate change perspective, the trend towards higher August rainfall recorded in our study area may alter oviposition phenology, with the subsequent cascade effects on weevil body size and fitness
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; adult emergence; Curculio; oviposition; Phenology; stochastic events; Temperature; timing of reproduction

Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Sardans, Jordi; Llusia, Joan (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.
Keywords: fertilization; Pinus halepensis; Quercus ilex; Temperature; terpene concentration; water stress

Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Sardans, Jordi; Llusia, Joan (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.
Keywords: fertilization; Pinus halepensis; Quercus ilex; Temperature; terpene concentration; water stress

Forest pathogens with higher damage potential due to climate change in Europe - La Porta, N; Capretti, P; Thomsen, I M; Kasanen, R; Hietala, A M; Von Weissenberg, K (Canadian Journal of Plant Pathology, 2008)
Abstract Most atmospheric scientists agree that climate changes are going to increase the mean temperature in Europe with increased frequency of climatic extremes, such as drought, floods, and storms. Under such conditions, there is high probability that forests will be subject to increased frequency and intensity of stress due to climatic extremes. Therefore, impacts of climate change on forest health should be carefully evaluated. Given these assumptions, several fungal diseases on trees may become more devastating because of the following factors: (i) abiotic stresses, such as drought and flooding, are known to predispose trees to several pathogens; (ii) temperature and moisture affect pathogen sporulation and dispersal, and changes in climatic conditions are likely to favour certain pathogens; (iii) migration of pathogens triggered by climatic change may increase disease incidence or geographical range, when pathogens encounter new hosts and (or) new potential vectors; and (iv) new threats may appear either because of a change in tree species composition or because of invasive species. If infection success is dependent on temperature, higher mean temperatures may lead to more attacks. Pathogens that have been of importance in southern Europe may spread northward and also upward to mountains. Pathogens with evolutionary potential for greater damage should be identified to estimate the magnitude of the threat and to prepare for the changing conditions. A review of the above-mentioned cases is presented. Some priorities to improve the ability to predict impacts of climate change on tree diseases are discussed.
doi: 10.1080/07060661.2008.10540534
Keywords: Drought; epidemiology; forest diseases; Global change; Global warming; opportunistic fungi; pathogenic fungi; predisposition; review; Temperature; water stress

Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 - Faria, T; Vaz, M; Schwanz, P; PolIe, A (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.
Keywords: catalase; Elevated CO2; photosynthesis; Quercus suber L.; superoxide dismutase; Temperature

Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 - FARIA, T.; Vaz, M.; Schwanz, P.; PolIe, A. (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.
Keywords: catalase; Elevated CO2; photosynthesis; Quercus suber L.; superoxide dismutase; Temperature

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

Refining vegetation simulation models: From plant functional types to bioclimatic affinity groups of plants - Laurent, J.-M.; Bar-Hen, A; François, L; Ghislain, M; Cheddadi, R (Journal of Vegetation Science, 2004)
Question: How to refine simulations based on a global vegetation model in order to apply it to regional scale? Location: Europe from 35° N to 71° N and 25° W to 70° E. Methods: Geographical ranges of European plants were georeferenced and used with monthly mean climatic data (diurnal temperature ranges, ground frost frequencies, precipitation, relative humidity, rain frequencies, amount of sunshine hours and temperature) and growing degree days to infer climatic boundaries for 320 taxa. We performed a discriminant analysis to define their potential geographic ranges. Hierarchical clustering was computed on potential ranges. Results: Clustering provided 25 Bioclimatic Affinity Groups (BAG) of plants consisting of 13 tree, seven shrub and five herb groups. These B AGs are characterized by different geographical ranges and climatic tolerances and requirements. Conclusion: The use of monthly data instead of annual values improved the prediction of potential distribution ranges and highlighted the importance of climate seasonality for defining the plant groups with accuracy. The B AGs are detailed enough to provide finer reconstructions and simulations of the vegetation at the regional scale.
Keywords: CARAIB; Discriminant analysis; Hierarchical clusteranalysis; Moisture; pollen; Seasonality; Temperature; Vegetation distribution

Refining vegetation simulation models: From plant functional types to bioclimatic affinity groups of plants - Laurent, J.-M.; Bar-Hen, A.; François, L.; Ghislain, M.; Cheddadi, R. (Journal of Vegetation Science, 2004)
Question: How to refine simulations based on a global vegetation model in order to apply it to regional scale? Location: Europe from 35° N to 71° N and 25° W to 70° E. Methods: Geographical ranges of European plants were georeferenced and used with monthly mean climatic data (diurnal temperature ranges, ground frost frequencies, precipitation, relative humidity, rain frequencies, amount of sunshine hours and temperature) and growing degree days to infer climatic boundaries for 320 taxa. We performed a discriminant analysis to define their potential geographic ranges. Hierarchical clustering was computed on potential ranges. Results: Clustering provided 25 Bioclimatic Affinity Groups (BAG) of plants consisting of 13 tree, seven shrub and five herb groups. These B AGs are characterized by different geographical ranges and climatic tolerances and requirements. Conclusion: The use of monthly data instead of annual values improved the prediction of potential distribution ranges and highlighted the importance of climate seasonality for defining the plant groups with accuracy. The B AGs are detailed enough to provide finer reconstructions and simulations of the vegetation at the regional scale.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CARAIB; Discriminant analysis; Hierarchical clusteranalysis; Moisture; pollen; Seasonality; Temperature; Vegetation distribution

Cryopreservation of Quercus suber and Quercus ilex embryonic axes: in vitro culture, desiccation and cooling factors. - Gonzalez-Benito, M Elena; Prieto, Roberto-Moreno; Herradon, Esther; Martin, Carmen (Cryo letters, 2002)
This study examines different factors included in the cryopreservation protocols for Quercus ilex and Q. suber embryonic axes. In vitro incubation temperature played an important role in the appropriate development of Q. ilex axes, as 15 degrees C was superior to 25 degrees C. Q. suber axes proved to be more sensitive to desiccation and cooling. Poor survival (35%) was observed when axes were included into cryovials and then in liquid nitrogen, and none when immersed in sub-cooled liquid nitrogen (-210 degrees C). Q. ilex axes showed poorly organised development in vitro (c. 50% of non-cooled axes showed shoot development). However, c. 80% survival was observed after cryopreservation (either in liquid nitrogen or sub-cooled liquid nitrogen at 0.34 g water / g dry weight), of which c. 15% showed shoot development.
Keywords: Cryopreservation; Cryopreservation: methods; Cryoprotective Agents; Cryoprotective Agents: pharmacology; Culture Techniques; Culture Techniques: methods; Desiccation; Desiccation: methods; embryonic axes; germination; germination temperature; Germination: drug effects; liquid nitrogen; plantlet development; Quercus; Quercus: embryology; Seeds; Seeds: chemistry; Seeds: embryology; Survival Rate; Temperature; water; Water: analysis

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Photosynthesis as a temperature indicator in Quercus ilex L. - Gratani, L; Pesoli, P; Crescente, M F; Aichner, K; LARCHER, W (Global and Planetary Change, 2000)
Net photosynthesis Pn , stomatal conductance gs , leaf temperature LT , transpiration rate . . . . E and in vivo chlorophyll fluorescence were monitored February 1996–February 1997 in Quercus ilex plants growing in the climax area Rome and . in the Garda lake region. Photosynthetic activity is an appropriate temperature-dependent functional trait linked to plant metabolism and performance. We employed photosynthesis as a stress temperature indicator. Regression analysis showed that in such regional climatic conditions, net photosynthetic rates were primarily correlated with temperature. The introduction of rainfall in the function did not significantly improve the theoretical prevision, in the range of temperature and rainfall analysed. The favourable leaf temperatures allowing 90–100% of the highest photosynthetic rates were 14–288C, decreasing over 50% when leaf temperature were respectively below 68C and over 378C: the low potential photochemical efficiency of 0.71 PSII Fv . rFm at Castelporziano during summer, confirmed the state of stress. Transpiration rates remained high with the increase of leaf temperature in summer, in spite of the 46% decrease of stomatal conductance. Nevertheless, this decrease allowed the maintenance of acceptable Pn rates in stressful conditions. The potential productivity of Q. ilex lied on high peaks of activity during periods of lower evaporative demand and a rapid stomatal response to an increase in air temperature and soil water deficit. Although it is difficult to forecast Q. ilex productivity and plant structure, we may hypothesize its future presence in the Mediterranean Basin by the capability of vegetative activity in a wide range of temperatures, the high stomatal control in stressful conditions, the high plasticity index and water use efficiency WUE .
Keywords: climatic change; in vivo chlorophyll fluorescence; photosynthesis; Quercus ilex; Temperature

Seasonal patterns of terpene content and emission from seven Mediterranean woody species in field conditions - Llusia, J.; Penuelas, J. (AMERICAN JOURNAL OF BOTANY, 2000)
The seasonal pattern of terpene content and emission by seven Mediterranean woody species was studied under field conditions. Emission rates were normalized at 30 degrees C and 1000 mu mol.m(-2).s(-1) PFD (photosynthetic photon Aux density). Bupleurum fruticosum, Pinus halepensis, and Cistus albidus stored large amounts of terpenes (0.01-1.77% \{[\}dry matter]) with maximum values in autumn and minimum values in spring. They emitted large amounts of terpenes (2-40 mu g.g DM-1.h(-1)), but with no clear seasonal trend except for Cistus albidus, which had maximum values in spring and minimum values in autumn. The nonstoring species Arbutus unedo, Erica arborea, Quercus coccifera and Quercus ilex also emitted large amounts of terpenes (0-40 mu g.g DM-1.h(-1)) and also tended to present maximum emission rates in spring, although this trend was significant only for A. unedo. At the seasonal scale, emission rates did not follow changes in photosynthetic rates; instead, they mostly followed changes in temperature. From autumn to spring, the least volatile monoterpenes such as limonene were emitted at highest rates, whereas the most volatile monoterpenes such as ol-pinene and P-pinene were the most emitted in summer. The monoterpene emission rates represented a greater percentage of the photosynthetic carbon fixation in summer (from 0.51% in Arbutus unedo to 5.64% in Quercus coccifera) than in the rest of the seasons. All these seasonality trends must be considered when inventorying and modeling annual emission rates in Mediterranean ecosystems.
The following values have no corresponding Zotero field: pub-location: OHIO STATE UNIV-DEPT BOTANY 1735 NEIL AVE, COLUMBUS, OH 43210 USA publisher: BOTANICAL SOC AMER INC
Keywords: alpha-pinene; limonene; mediterranean woody species; photosynthetic rate; relative humidity; Seasonality; Temperature; terpene emission and storage; volatility

Seasonal emission of monoterpenes by the Mediterranean tree Quercus ilex in field conditions: Relations with photosynthetic rates, temperature and volatility - Penuelas, Josep; Llusia, Joan (Physiologia Plantarum, 1999)
The relationships of monoterpene emission with temperature, light, photosynthesis and stomatal conductance (gs) were studied in Quercus ilex L. trees throughout the four annual seasons under field conditions. The highest monoterpene emission was measured in spring and summer (midday average of 11 μg [g DW]−1 h−1), whereas the lowest rates were found in autumn and winter (midday averages of 0.51 and 0.23 μg [g DW]−1 h−1, respectively). In spring and summer, limonene was the monoterpene emitted at highest rate (midday averages of 5.27–6.69 μg [g DW]−1 h−1), whereas α-pinene was emitted the most in autumn and winter (midday averages of 0.31 μg [g DW]−1 h−1). The monoterpenes limonene, α-pinene and β-pinene represented about 75–95% of total detected monoterpenes. The total monoterpene emission rates represented about 0.04% of carbon fixed in autumn, 0.17% in winter, 0.84–2.51% in spring and 1.22–5.13% in summer. Significant correlations of total monoterpene emission with temperature were found when considering either summer emission or the emission over the entire year, whereas significant correlations with net photosynthetic rates were only found when considering summer season. Among individual terpenes, the most volatile, α-pinene and β-pinene, were more correlated with temperature than with net photosynthetic rates whereas the less volatile limonene was more correlated with net photosynthetic rate. Thus, under field conditions it seems that dependency of monoterpene emission on photosynthetic rate or temperature is partly related with volatility of the compounds. Influences of seasonality, temperature, photosynthetic rates and volatility should be considered in inventories and models of emission rates in Mediterranean ecosystems.
Keywords: monoterpene emission rates; photosynthetic rates; seasonal variation (voyant); Temperature; volatility

Short-term responses of terpene emission rates to experimental changes of PFD in Pinus halepensis and Quercus ilex in summer field conditions - Penuelas, J.; Llusia, J. (Environmental and Experimental Botany, 1999)
The diurnal relationships of monoterpene emission with PFD and photosynthetic rates were studied in the Mediterranean trees Pinus halepensis, a terpene storing species, and Quercus ilex, a non-storing species, under summer ﬁeld conditions. At morning, midday and evening, leaves were submitted to different irradiance levels by differentially shading them. Both species emitted large amounts of monoterpenes (about 20 mg g DM1 h1 ). The most emitted terpene by P. halepensis was D 3 -carene followed by b-myrcene, a-pinene and b-pinene. The most emitted terpene by Q. ilex was limonene followed by a-pinene and b-pinene. No clear correlation to temperature was found for Q. ilex emission within the diurnal range of 21–33°C, whereas P. halepensis emissions increased with the temperature. There was no consistent link between terpene emissions and PFD or photosynthetic rates for P. halepensis but there were signiﬁcant relationships for Q. ilex. However, emissions by Q. ilex became inhibited at highest PFDs and during the course of the day when net photosynthesis decreased under summer drought. The study shows that the emission rates of both species are highly variable and that during a hot Mediterranean summer day (with limited water availability) the diurnal variation of emission is not only driven by the common light and temperature dependencies. Water stress, branch-to-branch variability and other inﬂuences must explain great part of the observed variability
Keywords: a-pinene; d 3 -carene; field conditions; limonene; pfd; photosynthetic rate; Pinus halepensis; Quercus ilex; Temperature; Terpene emission

Short-term responses of terpene emission rates to experimental changes of PFD in Pinus halepensis and Quercus ilex in summer field conditions - Penuelas, J; Llusia, J (Environmental and Experimental Botany, 1999)
The diurnal relationships of monoterpene emission with PFD and photosynthetic rates were studied in the Mediterranean trees Pinus halepensis, a terpene storing species, and Quercus ilex, a non-storing species, under summer ﬁeld conditions. At morning, midday and evening, leaves were submitted to different irradiance levels by differentially shading them. Both species emitted large amounts of monoterpenes (about 20 mg g DM1 h1 ). The most emitted terpene by P. halepensis was D 3 -carene followed by b-myrcene, a-pinene and b-pinene. The most emitted terpene by Q. ilex was limonene followed by a-pinene and b-pinene. No clear correlation to temperature was found for Q. ilex emission within the diurnal range of 21–33°C, whereas P. halepensis emissions increased with the temperature. There was no consistent link between terpene emissions and PFD or photosynthetic rates for P. halepensis but there were signiﬁcant relationships for Q. ilex. However, emissions by Q. ilex became inhibited at highest PFDs and during the course of the day when net photosynthesis decreased under summer drought. The study shows that the emission rates of both species are highly variable and that during a hot Mediterranean summer day (with limited water availability) the diurnal variation of emission is not only driven by the common light and temperature dependencies. Water stress, branch-to-branch variability and other inﬂuences must explain great part of the observed variability
Keywords: a-pinene; d 3 -carene; field conditions; limonene; pfd; photosynthetic rate; Pinus halepensis; Quercus ilex; Temperature; Terpene emission

Climatic classification and ordination of the Spanish Sistema Central: relationships with potential vegetation - Gavilán, R G; Fernández-González, F; Blasi, C (Plant Ecology, 1998)
Monthly precipitation and monthly mean temperature records from 255 meteorological stations in Central Spain (Spanish Sistema Central) were analyzed by cluster and principal component analyses. Classiﬁcation separated 14 groups according to altitude, geographical distribution, as well as the combination of rainfall and temperature. The ﬁrst cluster emerged as signiﬁcantly higher and colder than the second. Then, two ordinations were carried out: one for the 14 groups extracted from the classiﬁcation and a second for the total station pool. The second ordination was compared with potential natural vegetation data taken around each station. The ﬁrst ordination summarized the principal climatic characteristics of the Spanish Sistema Central: its behaviour is that of a typical Mediterranean mountainous territory combining summer aridity and variation of temperature with altitude and the inﬂuence of winter winds. The ordination of all stations reﬂected a thermal, rainfall and summer aridity gradient. Meteorological stations situated at the highest altitude or with highest precipitation records characterized by scrub communities or pine woods and Quercus pyrenaica forests, appeared well-separated along the ﬁrst two axes. Only the most thermophilous Q. rotundifolia associations could be clearly separated. The fourth axis was useful in clarifying some vegetation overlap of deciduous and sclerophyllous forests, along an east-west summer aridity gradient.
Keywords: climate; cluster analysis; potential vegetation; Precipitation; Principal component analysis; Spain; Temperature

The aquatic processing of sclerophyllous and malacophyllous leaves on a Mediterranean island (Corsica) : spatial and temporal pattern - Schwarz, A E; Schwoerbel, J (Annales de Limnologie - International Journal of Limnology, 1997)
Leaves of two species, alder (Alnus glutinosa) and holm-oak (Quercus ilex), were exposed in bags of two mesh sizes in two climatically contrasting sites of a Corsican softwater stream. Leaves were incubated both in winter and in summer for about 6 months. The field experiment was designed to determine the influence of both spatial (climate) and temporal (season) variations of temperature, as well as differences in the chemical and physical properties of sclerophyilous and malacophyllous leaves, on leaf decomposition rates. Comparisons were made between leaves colonized by macroinvertebrates and leaves protected by finemesh. In winter and summer, holm-oak leaves were colonized much less by macroinvertebrates than alder leaves. Spatial and temporal differences in leaf litter processing were mainly dependent on three factors (i) the chemical and physical properties of the leaves, (ii) the abundance of macroinvertebrates in the sediment and (iii) the temperature. The climatical pattern of temperature had a greater influence than its seasonal pattern. In contrast with many other studies, abiotic factors dominated over biotic factors in this study.
Keywords: alnus glutinosa; decomposition; leaves; macroinvertebrates; Mediterranean ecosystem; Quercus ilex; Temperature

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS - Kesselmeier, J; Bode, K; Hofmann, U; Mtjller, H; Schafer, L; Wolf, A; Ciccioli, P; Cecinato, A; Frattoni, M; Foster, P; Dutaur, L; Torreq, L (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects
Keywords: aldehydes; carbon budget; coniferous; deciduous; light; Monoterpenes; oak; organic acids; pine; Pinus pinea L; Plant physiology; Quercus ilex L; Temperature; Volatile Organic Compounds

Use of the isoprene algorithm for predicting the monoterpene emission from the Mediterranean holm oak Quercus ilex L.: Performance and limits of this approach - Ciccioli, Paolo; Fabozzi, Concetta; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano; Loreto, Francesco; Kesselmeier, Jürgen; Schäfer, Luise; Bode, Kirsten; Torres, Liberto; Fugit, Jean-Luc (Journal of Geophysical Research: Atmospheres, 1997)
The algorithm developed by Guenther et al. [1991] to describe the organic emission of isoprene-emitting plants has been used for predicting monoterpene emission from Quercus ilex L., an evergreen oak typical of the Mediterranean basin. The dependence of monoterpene emission on photosynthetically active radiation and temperature has been verified through laboratory experiments carried out on single leaves as well as through field measurements at branch level. While the algorithm describes well monoterpene emission under stationary state conditions, it is less accurate when rapid fluctuations of light and temperature take place. Because of this, the isoprene algorithm is capable of predicting the response of Quercus ilex L. with an accuracy better than ±25% only in 65% of the environmental situations experienced by the plant. Field and laboratory observations consistently indicate that temperature oscillations can be an important source for the discrepancies between predicted and observed values as they can generate bursts of emission with values twice as high as those predicted by the algorithm. Possible causes generating these effects are analyzed and critically discussed. In spite of the observed limitations, the isoprene algorithm can successfully describe the biogenic emission from Quercus ilex L., and its use is advantageous as it greatly simplifies regional and global emission models, especially if the light dependence of monoterpene emission is proven to be a widespread phenomenon.
Keywords: Biogenic emission; isoprene algorithm; monoterpene (voyant); Quercus ilex; Temperature

Use of the isoprene algorithm for predicting the monoterpene emission from the Mediterranean holm oak Quercus ilex L.: Performance and limits of this approach - Ciccioli, Paolo; Fabozzi, Concetta; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano; Loreto, Francesco; Kesselmeier, Jürgen; Schäfer, Luise; Bode, Kirsten; Torres, Liberto; Fugit, Jean-Luc (Journal of Geophysical Research: Atmospheres, 1997)
The algorithm developed by Guenther et al. [1991] to describe the organic emission of isoprene-emitting plants has been used for predicting monoterpene emission from Quercus ilex L., an evergreen oak typical of the Mediterranean basin. The dependence of monoterpene emission on photosynthetically active radiation and temperature has been verified through laboratory experiments carried out on single leaves as well as through field measurements at branch level. While the algorithm describes well monoterpene emission under stationary state conditions, it is less accurate when rapid fluctuations of light and temperature take place. Because of this, the isoprene algorithm is capable of predicting the response of Quercus ilex L. with an accuracy better than ±25% only in 65% of the environmental situations experienced by the plant. Field and laboratory observations consistently indicate that temperature oscillations can be an important source for the discrepancies between predicted and observed values as they can generate bursts of emission with values twice as high as those predicted by the algorithm. Possible causes generating these effects are analyzed and critically discussed. In spite of the observed limitations, the isoprene algorithm can successfully describe the biogenic emission from Quercus ilex L., and its use is advantageous as it greatly simplifies regional and global emission models, especially if the light dependence of monoterpene emission is proven to be a widespread phenomenon.
Keywords: Biogenic emission; isoprene algorithm; monoterpene (voyant); Quercus ilex; Temperature

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - Faria, T; Wilkins, D; Besford, R T; Vaz, M; Pereira, J S; Chaves, M M (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature

Changes in litter during the initial leaching phase: an experiment on the leaf litter of Mediterranean species - Ibrahima, Adamou; Joffre, Richard; Gillon, Dominique (Soil biology and biochemistry, 1995)
A laboratory experiment was carried out with the litter of 7 Mediterranean species of plants to compare their mass losses during the initial leaching phase of decomposition. To this end, the leaf and needle litter of deciduous, marcescent (deciduous species in which the withered leaves remain on the tree. for several months) and evergreen broad-leaved species and pine was immersed for 10 days in demineralized water, in the dark at 22°C. Samples were taken at 1,6, 24,72, 168 and 240 h. Depending on the species, the litter lost between ‘T-15% of initial dry mass, and water content values were between 130-360% of dry mass. The water absorption rate was positively correlated with the initial cellulose content of the litter and negatively correlated wil:h the initial leaf density, but the water content at the end of the experiment, the leaching rate and the total mass loss were uncorrelated with any of the initial litter characteristics studied. For 100 g of litter at the start (as dry matter), the losses after 240 h of immersion in water were, when they were significant, 5-8 g of C, 70-l 30 mg of N (significant for 3 species), 4-40 mg of soluble sugars and 3 g of inorganic elements (significant for only 2 species). In contrast, the quantities of lignin and cellulose in the litter remained unchanged. Most of the leaching losses (SCrSO%) therefore consisted of C. During leaching, the litter showed a tendency to become more concentrated in cellulose and lignin and poorer in sugars. Pine needle litter was distinguished by its low water absorption and low mass loss during leaching. In general, the litters of deciduous species were more absorbent than the litters of evergreen species. In contrast, the losses of water-soluble substances were not significantly different between these 2 groups of litters. In the broad-leaved species, the losses of water-soluble substances were slower and 2-3 times lower, compared to results already published for species from mesic biomes
Keywords: litter decomposition; mediterranean species; Temperature; water availability (voyant)

INFLUENCIA DE LAS COBERTURAS DE ENCINAS , Quercus ilex subsp. ballota , EN LA ROTURA DE LOS PERFILES TERMICOS VERTICALES - Escudero Garcia, J. C.; Cabezas Fernández, J.; Lavado Contador, F. (CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993, 1993)
Vegetation cover acts intensely on vertical temperature profiles, breaking up their structure. For the particular case of holm oak parkland (dehesas) forests systems, these will affect the vertical temperature gradient by modifying it more or less sharply as a function funtamenta1ly of the height and characteristics of the canopy, the density of trees ánd of foliage load. The study was carried in Cheles (Badajoz), and consisted in periodic measurements of the temperature variations in the profile. The results show quantitatively the influence of arboreal systems on the vertical structure of air and soil temperatures. A characterlzation is thereJore given of the thermal impact that intense pruning and destruction of holm oaks have on the vertical profIle, especially that of he soil.
The following values have no corresponding Zotero field: periodical: CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993
Keywords: gradients; impact; Quercus ilex; Temperature

INFLUENCIA DE LAS COBERTURAS DE ENCINAS , Quercus ilex subsp. ballota , EN LA ROTURA DE LOS PERFILES TERMICOS VERTICALES - Escudero Garcia, J C; Cabezas Fernández, J; Lavado Contador, F (CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993, 1993)
Vegetation cover acts intensely on vertical temperature profiles, breaking up their structure. For the particular case of holm oak parkland (dehesas) forests systems, these will affect the vertical temperature gradient by modifying it more or less sharply as a function funtamenta1ly of the height and characteristics of the canopy, the density of trees ánd of foliage load. The study was carried in Cheles (Badajoz), and consisted in periodic measurements of the temperature variations in the profile. The results show quantitatively the influence of arboreal systems on the vertical structure of air and soil temperatures. A characterlzation is thereJore given of the thermal impact that intense pruning and destruction of holm oaks have on the vertical profIle, especially that of he soil.
Keywords: gradients; impact; Quercus ilex; Temperature

Mediterranean pasture dynamics: the role of germination - Espigares, T; Peco, B (Journal of Vegetation Science, 1993)
pastures were arranged along a gradient of sensitivity to temperature on the arrival of the first persistent rain. This sensitivity was manifested in both the total germination success of the species and the germination time profile. The different germination patterns of the species can provide competitive advantages depending on the autumn weather conditions.
Keywords: Autumn rain; Gradient; Phytotron; seed bank; Temperature; Weather fluctuation

Mediterranean pasture dynamics: the role of germination - Espigares, T.; Peco, B. (Journal of Vegetation Science, 1993)
pastures were arranged along a gradient of sensitivity to temperature on the arrival of the first persistent rain. This sensitivity was manifested in both the total germination success of the species and the germination time profile. The different germination patterns of the species can provide competitive advantages depending on the autumn weather conditions.
Keywords: Autumn rain; Gradient; Phytotron; seed bank; Temperature; Weather fluctuation

Relationship between temperature and the timing of breeding of the blue tit (Parus caeruleus) in two Mediterranean oakwoods - Bellot, M D; Dervieux, Alain; Isenmann, Paul (Journal of Ornithology, 1991)
They think that these temperatures have an influence on the timing of breeding but it remains unclear if this influence is direct or indirect. In this study, we present the results of an investigation of the effect of temperature on the timing of breeding of a population of Blue Tits (Parus caeruleus) breeding in two neighbouring oakwoods, one dominated by evergreen Holm Oaks, the other by deciduous Downy Oaks in Mediterranean France. Though experiencing the same climate, this population shows marked variation between individuals for laying time (BLoNDEL et al. 1987, CLAMENS & ISENMANN 1989, DERVIEUX et al. 1990). In this con- text, two questions are considered: 1) is there a relationship between temperature and laying date in the two oakwoods and, 2) how may temperature cause such variation?
Keywords: breeding; egg laying; Parus caeruleus (voyant); Temperature

Variations de la croissance radiale de Quercus ilex L en fonction du climat - Zhang, S H; Romane, F (Ann. For. Sci., 1991)
Diameter growth of Quercus ilex L and the interannual variability of climatic characteristics. Diameter growth of Quercus ilex L, the dominant sclerophyllous species in much of the Mediterranean basin vegetation, was studied in relation to precipitation and temperature. The study site in Montpellier (Southern France) has a Mediterranean climate. Eleven trees, grown from acorns in 1963, were cut in 1984 and the rings studied at 3 levels (ground, 0.5 and 1 m above the ground). The data were analyzed by the ARMA procedure which gives the part of the total variation due to the autocorrelation processes. A multiple regression between the factors of a principal component analysis (PCA) of the monthly climatic data (rainfall and temperature) and the residuals issuing from the ARMA procedure then suggested that the large annual rings were due to a particular rainfall distribution during the year, the late summer precipitation promoting a large annual growth diameter (table II). The presence or absence of false rings (table I) was also analyzed by PCA (figs 2 and 3). The false rings were positively correlated to a large annual growth diameter corresponding to a high summer rainfall (fig 4), while the relationship with the temperature preceding the growing season was negative. It therefore appears that this species is relatively unaffected by spring climatic conditions, ie which generally indicate the main growth phase, but that it is able to take advantage of the interannual climatic variations of the region.
Keywords: diameter growth; Mediterranean climate; Precipitation; Quercus ilex L; ring; Temperature

Etude de l'appareil radical de jeunes plants de Chênes verts dont le pivot se développe sans amputation, ni déviation - BEISSALAH, Y; AMIN, T; EL HAJZEIN, B; NEVILLE, P; BERNARD, Janine (Ann. For. Sci., 1988)
The experimental study of the root system of woody plants is far behind that of the aerial system. To make up for this difference, a study was begun on a Mediterranean sclerophyllous oak (Quercus ilex L.). The present study defines the developmental characteristics of the root system in young seedling whose tap root has neither been diverted nor amputated and which grows in different ecological conditions (substrates, temperatures). The results obtained can be used as an interpretative guide for the root system’s reactions to both diverting and amputating. These reactions will be described elsewhere. The study was made in R IEDACKER type minirhirotrons (1974) and L AMOND type fog chambers (1975). The root system of holly oak seedlings (fig. 1) consists of one main root (tap root) with positive geotropism and rapid and theoretically unlimited growth, from which thin, usually short, branch roots, either subhorizontal or oblique with slow, limited growth, spread out (fig. 5). The tap root is not rectilinear, but ondulates more or less regulary (fig. 1), both in loosely-packed substrates (peat ou loam) and in the absence of any substrate (fog chamber). The substrate’s resistance to root penetration, therefore, does not cause these ondulations. The largest branch roots generally begin growth on the convex part of the ondulation (fig. 1, B and C). The tap root grows better in peat than in loam or fog chambers (fig. 2). Its growth is subject to different types of fluctuations (fig. 4). It is highly sensitive to thermic variations (fig. 2 and 3). A 5 °C temperature drop (from 25 °C to 20 °C) decreases its growth rate by a quarter in peat and by half in loam (fig. 2). This decrease is lower in fog chambers because of their neutralizing effect. The tap root’s growth rate also fluctuates regardless of temperature, substrate (peat or loam), or lack of substrate (fig. 4). The fluctuation period varies from 2 to 7 days and is probably the expression of an irregular endogenetic rythm. Systematic ablation of branch roots as they appear has not effect on the variations in the tap root’s growth rate. Anatomy also differentiates the tap root from branch roots. The tap root usually has 6 major xylem fascicles (more rarely 4 to 8) directly underneath the cotyledons and connected to them in groups of three per cotyledon (fig. 6). Between these are often extra xylem fascicles which are smaller, connected to the epicotyle and disappear rapidly lower down (fig. 7, A and A’). The major xylem fascicles divide between the 3‘d and T&dquo; centimeter from the cotyledon by enlarging and isolating their wings (fig. 7, A and B) which can result at most in a tripling of the number of xylcm fascicles. These additional fascicles vanish progressively either by fusion and/or reduction up to the 20’&dquo; centimeter from the cotyledon (fig. 7, C). Beyond this, we find the same number of xylem fascicles as at the start, i.e. only major fascicles remain (fig. 7, D). The number of phloem fascicles, at first twice that of the major xylem fascicles in the area of the tap root near the cotyledons (fig. 7, A and B), decreases progressively, generally by fusion, until it equals the latter beyond the 20’&dquo; centimeter from the cotyledon (fig. 7, D). This remarkable fluctuation in fascicle number is probably related to the period of cotyledon influence. It is not present in the branch roots, which have between 3 and 5 xylem fascicles alternating with an equal number of phloem fascicles.
Keywords: development; Quercus ilex; rool; Seedling; Temperature; vascular bundles

Influence of Temperature on the Effects of Water Stress on Quercus Species - SPYROPOULOS, C G; LAMBIRIS, M P (Annals of Botany, 1979)
Quercus coccifera L. and Q. ilex L. leaves, collected in winter, when the plants were in full turgor, were treated with polyethylene glycol (PEG) with a water potential of −48 and −65 bar, at 15 °C and at 30 °C, for 2 days. The response of each species differs with temperature as far as the plastid pigment, anthocyanin and soluble sugar content is concerned. Thus Q. ilex is affected more at 15 °C rather than at 30 °C, while in Q. coccifera, apart from a small increase in anthocyanins, no significant change was observed at 15 °C. On the contrary, at 30 °C significant changes were observed in all studied parameters. Chloroplast pigments decreased generally on the first day and their content either dropped further or increased to reach the control values on the second day. All treatments resulted in an increase in anthocyanin content. Soluble sugar content raised in Q. ilex at 15 °C and decreased in both species at 30 °C.
Keywords: anthocyanin; carotenoids; chlorophyll; oak; Quercus coccifera; Quercus ilex; Temperature; water stress